2019
DOI: 10.3390/agronomy9090474
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Drying Temperature on the Phenolic Content and Functional Behavior of Flours Obtained from Lemon Wastes

Abstract: Lemon processing generates thousands of tons of residues that can be preserved as flours by thermal treatment to obtain phenolic compounds with beneficial bioactivities. In this study, the effect of different drying temperatures (40, 50, 60, 70, 80, 90, 100 and 110 °C) on the Total Phenolic Content (TPC), antioxidant and antimicrobial activities of phenolic compounds present in Citrus. lemon (L.) Burn f waste was determined. Identification and quantification of phenolic compounds were also performed by UPLC-PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…Many studies indicate that aglycones exhibit higher antioxidant activity than their glycosidic forms or those linked by other types of bonds [ 18 , 19 , 20 ]. The antioxidant activity of polyphenols also depends on the number of hydroxyl groups in the molecule, and it can be enhanced by spherical effects as well as synergistic and antagonistic interactions with compounds present in the matrix [ 20 , 21 ]. Hence, a higher content of polyphenolic compounds does not always cause improvement of antioxidant properties.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies indicate that aglycones exhibit higher antioxidant activity than their glycosidic forms or those linked by other types of bonds [ 18 , 19 , 20 ]. The antioxidant activity of polyphenols also depends on the number of hydroxyl groups in the molecule, and it can be enhanced by spherical effects as well as synergistic and antagonistic interactions with compounds present in the matrix [ 20 , 21 ]. Hence, a higher content of polyphenolic compounds does not always cause improvement of antioxidant properties.…”
Section: Resultsmentioning
confidence: 99%
“…Previous experiments have shown that aglycones have a higher antioxidant activity than their glycosidic forms or those connected by different types of bonds [ 20 , 21 ]. Moreover, research has indicated that the antioxidant activity of polyphenols is dependent on the number of hydroxyl groups in the molecule and can be enhanced by spherical effects, as well as by synergistic and antagonistic interactions of the compounds present in the matrix and in the extracts [ 22 , 23 ]. Thus, an increase in the content of polyphenolic compounds does not always entail an increase in antioxidant properties.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, polyphenol concentration can vary due to food processing or drying because of the early degradation of phenolic compounds that is favored by high temperature and prolonged exposure to heat. This brings about the release of phenolic substances through breakage of ether, ester or acetal covalent bonds [ 22 ]. Mutari et al [ 20 ] suggest that high temperature treatment can improve the solubility of phenolic compounds leading to the breakdown of cellular structures and improving the release of phenolic compounds (including phenolic acids) previously bound to the macromolecules of the cell wall.…”
Section: Resultsmentioning
confidence: 99%
“…Orange fruits ( Citrus aurantium ) were purchased from a local market in Yucatán, México. In order to obtain a raw material that can be used in the extraction of value-added chemicals and in the synthesis of biochars, sour oranges were peeled (SOP), and the fresh peels were shredded and dried in a steam dehydrator (Jersa 148-09, Ciudad de México, México) with air circulation at 45 °C for 24 h. The drying conditions were fixed to favor the extraction of significant amounts of value-added chemicals such as polyphenols from SOP [ 18 ]. Subsequently, the sour orange peels were finely ground (Pulvex 200 grinder, Ciudad de México, Mexico) and passed through a < 0.500 mm metal sieve.…”
Section: Methodsmentioning
confidence: 99%